Naughty By Nurture: Black Male Joyriding—Is Everything Gonna Be Alright? - Greene, Dwight L. (Columbia Journal of Gender and Law, 1994)
This Article is the final work of Professor Greene’s extensive contribution to the study of the intersection of law and race. Professor Greene was still in the process of developing this work when he was murdered on July 5, 1993. The Journal collaborated with Professor Greene’s friend and colleague, Professor Twyla Tharp of Rutgers University, and made only minimal editorial changes in this Article to preserve the integrity of the author’s voice.